Partner Choice, Investment in Children, and the Marital College Premium - Chiappori, Pierre-André; Salanié, Bernard; Weiss, Yoram (American Economic Review, 2017)
We construct a model of household decision-making in which agents consume a private and a public good, interpreted as children's welfare. Children's utility depends on their human capital, which depends on the time their parents spend with them and on the parents' human capital. We first show that as returns to human capital increase, couples at the top of the income distribution should spend more time with their children. This in turn should reinforce assortative matching, in a sense that we precisely define. We then embed the model into a transferable utility matching framework with random preferences, à la Choo and Siow (2006), which we estimate using US marriage data for individuals born between 1943 and 1972. We find that the preference for partners of the same education has significantly increased for white individuals, particularly for the highly educated. We find no evidence of such an increase for black individuals. Moreover, in line with theoretical predictions, we find that the “marital college-plus premium” has increased for women but not for men. (JEL D12, J12, J13, J15, J24)